Does the Anti-Mullerian Hormone Decline Rate Improve the Prediction of Age at Menopause? - Ramezani Tehrani, Fahimeh; Sheidaei, Ali; Firouzi, Faezeh; Tohidi, Maryam; Azizi, Fereidoun; Behboudi-Gandevani, Samira (Frontiers in Endocrinology, 2021)
Objectives: The result of studies assessed whether multiple anti Mullerian hormone (AMH) measurements can improve the individualized prediction of age at menopause in the general population had conflicting results. This study aimed to re-explore the additive role of decline rate of AMH to single AMH measurement, in improvement of prediction of age at menopause, using two common statistical models for analysis of time to event data including time-dependent cox regression and proportional hazard cox regression. Methods: A total of 957 eligible women aged 18–50 years were recruited from among Tehran Lipid and Glucose cohort Study participants and were followed-up every 3 years for a total of 18 years. Serum AMH was measured at the time of recruitment and twice after that at an average of 6-year intervals with the Gen II AMH assay. The additive value of repeated AMH measurements for prediction of age at menopause was explored using two different statistical approaches. In the first approach, the time-dependent cox model was used that included all three measurements of AMH as the time-varying predictors and the baseline age and the logarithm of annual AMH decline rate as the time-stationary. In the second approach, a proportional hazard Cox model was fitted to the baseline data and the improvement of complex model that included repeated AMH measurements and logarithm of annual AMH decline rate was assessed using C-statistics. Results: The time-dependent cox model showed that each unite increases in AMH level could reduce the hazard of menopause by 87%. The proportional hazard Cox model also improved the prediction of age at menopause by 3% according to C-statistics. The subgroup analysis for prediction of early menopause revealed that the hazard of early menopause increased by 10.8 for each unit increase the annual AMH decline rate. Conclusion: This study confirmed that compared to single AMH measurement, multiple AMH measurement could improve the prediction of individual risk of menopause. Different alternative statistical approaches may lead to same interpretations of findings if their essential assumptions are considered.